Consideration of Congestion Situations in Telecommunication Networks and Methods of Their Processing as a Special Type of Emergency Situations - Harutyunyan, Hamlet H.; Avanesyan, Hmayak A. (Mathematical Problems of Computer Science, 2021)
This article discusses the methods of struggle with congestion situations in telecommunication networks, considering them as a special type of emergency situations, which frequently occur in computing systems.